Analyzing Cyberbullying Negative Content on Twitter Social Media with the RoBERTa Method - Warih Maharani; Muh. Akib A. Yani (JINAV: Journal of Information and Visualization, 2023)
Social media is an online-based communication tool that can make it easier for users to interact among fellow users without any area and time restrictions. Indonesia has the highest number of social media users in the world. The Twitter social media platform is a place where users can pour out their whole hearts in the form of tweets. Free and diverse interactions on Twitter have a considerable influence on the psychological condition of its users. Cyberbullying or online bullying is an act of humiliating or hurting other people's feelings intentionally and repeatedly on social media, messages, or in other ways. In this study, the RoBERTa classification method was used to detect cyberbullying tweets with a best accuracy score of 86.9% and an f1-score of 77.5%.